2018
DOI: 10.33487/edumaspul.v2i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Teknik Regulasi Diri (self-regulation) untuk Meningkatkan Kemandirian Belajar Mahasiswa Program Studi Bimbingan Konseling STKIP Muhammadiyah Enrekang

Abstract: Penelitian Eksperimen ini dilakukan di Program Studi Bimbingan Konseling dengan subjek penelitian adalah Mahasiswa semester 3 dengan jumlah 10 orang. Masalah dalam penelitian ini adalah Mahasiswa semester 3 mengalami kemandirian belajar yang rendah. Rumusan masalah penelitian ini adalah (1) Bagaimana gambaran kemandirian belajar mahasiswa sebelum penerapan Teknik Regulasi diri di Program Studi Bimbingan Konseling. (2) Bagaimana gambaran pelaksanaan teknik regulasi diri untuk meningkatkan kemandirian belajar Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
0
6
0
10
Order By: Relevance
“…Another study found a positive and significant relationship with academic procrastination [14,15]. Yasdar [16], concluded that the application of the Self-Regulation Technique had a positive effect on learning independence, Putro [17] found that the level of student academic procrastination decreased significantly after attending group counseling with self-regulated learning techniques, and Kirana [18] concluded that selfregulation training regulated learning is effective in reducing students' academic procrastination. Other findings conclude that academic procrastination impacts inhibiting individual performance [7], and low achievement [6,8,13].…”
Section: Several Studies Conclude the Following Findingsmentioning
confidence: 99%
“…Another study found a positive and significant relationship with academic procrastination [14,15]. Yasdar [16], concluded that the application of the Self-Regulation Technique had a positive effect on learning independence, Putro [17] found that the level of student academic procrastination decreased significantly after attending group counseling with self-regulated learning techniques, and Kirana [18] concluded that selfregulation training regulated learning is effective in reducing students' academic procrastination. Other findings conclude that academic procrastination impacts inhibiting individual performance [7], and low achievement [6,8,13].…”
Section: Several Studies Conclude the Following Findingsmentioning
confidence: 99%
“…According to several types of research, to generate productivity, independence, and work motivation is a selfregulatory approach. This can be seen from the results of research by Yasdar and Muliyadi (2018). The application of Self-Regulation Techniques has a positive effect on learning independence.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Regulasi diri (self regulation) dapat diterapkan melalui latihan regulasi diri. Melalui perlakuan dengan teknik regulasi diri dapat memberi pengaruh positif terhadap kemandirian belajar (Yasdar & Muliyadi, 2018). Oleh karenanya, regulasi diri dapat menjadi strategi alternative dalam membangun kemandirian belajar siswa yang mewujud dalam beberapa hal seperti: mengatur jadwal belajar, menetapkan target belajar, dan mencari informasi yang dibutuhkan secara mandiri (Dinata, Rahzianta, & Zainuddin, 2016).…”
Section: Hasil a Flliped Learning Dalam Menumbuhkan Kemandirian Belajarunclassified